Ultrasound as a technology of reassurance?: how pregnant women and health care professionals articulate ultrasound reassurance and its limitations - Thomas, Gareth M.; Roberts, Julie; Griffiths, Frances E. (Blackwell Publishing, 2017)
The premise that ultrasound technologies provide reassurance for pregnant women is well-rehearsed. However, there has been little research about how this reassurance is articulated and understood by both expectant mothers and health care professionals. In this article, we draw on two qualitative UK studies to explore the salience of ultrasound reassurance to women's pregnancy experiences whilst highlighting issues around articulation and silence. Specifically, we capture how expectant parents express a general need for reassurance and how visualisation and the conduct of professionals have a crucial role to play in accomplishing a sense of reassurance. We also explore how professionals have ambiguities about the relationship between ultrasound and reassurance, and how they subsequently articulate reassurance to expectant mothers. By bringing two studies together, we take a broad perspectival view of how gaps and silences within the discourse of ultrasound reassurance leave the claims made for ultrasound as a technology of reassurance unchallenged. Finally, we explore the implications this can have for women's experiences of pregnancy and health care professionals’ practices.